Stability Enhancement of Islanding Event Through Boundary Detection and Voltage Stability Index - Tang A.S.; Ramachandaramurthy V.K.; Pouryekta A.; Padmanaban S.; Umashankar S. (Institute of Electrical and Electronics Engineers Inc., 2023)
Distributed power generation; MATLAB; Topology; Voltage control; Boundary detection; Boundary detection method; Distribution systems; Islanding; Load-shedding; Safety and stabilities; Stability enhancement; Voltage stability index; System stability